2022
DOI: 10.1002/pan3.10303
|View full text |Cite
|
Sign up to set email alerts
|

Nature relatedness: A protective factor for snake and spider fears and phobias

Abstract: 1. Worldwide, urbanization has created completely novel environments, which bring many conveniences but carry several drawbacks too. One of the most important disadvantages is that most people living in cities lose contact with nature including interaction with animals. Current evidence shows that countries with lower levels of urbanization also have a lower prevalence of animal fears and phobias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 168 publications
2
22
0
Order By: Relevance
“…Baseline analyses indicated that children who were more connected to nature before the intervention already had higher Wonder scores, which suggests a link between general connectedness to nature and attitudes towards individual species, regardless of whether the species is 'unpopular'. This could suggest that improving connectedness to nature could improve attitudes towards all wild animals, including 'unpopular' ones, which is supported by research by Zsido et al (2022). However, we found Dislike/fear towards adders was not associated with connectedness to nature, which may reflect snake-specific phobia or fear-based traits that are unrelated to whether the subjects were connected to nature…”
Section: Links Between Connectedness To Nature and Attitudes Towards ...supporting
confidence: 67%
See 2 more Smart Citations
“…Baseline analyses indicated that children who were more connected to nature before the intervention already had higher Wonder scores, which suggests a link between general connectedness to nature and attitudes towards individual species, regardless of whether the species is 'unpopular'. This could suggest that improving connectedness to nature could improve attitudes towards all wild animals, including 'unpopular' ones, which is supported by research by Zsido et al (2022). However, we found Dislike/fear towards adders was not associated with connectedness to nature, which may reflect snake-specific phobia or fear-based traits that are unrelated to whether the subjects were connected to nature…”
Section: Links Between Connectedness To Nature and Attitudes Towards ...supporting
confidence: 67%
“…Previous research has confirmed that increased nature connectedness is linked to pro-environmental behaviours in adulthood (Davis et al, 2009;Richardson et al, 2020;Zelinski et al, 2015) and to lower incidences of snake phobias (Zsido et al, 2022).…”
Section: Wider Implications For Conservation and Other Speciesmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, country-level indicators were also required for the negativistic grouping. These were included to tap into Kellert’s negativistic relationship type as there is evidence of relationship between higher levels of fear of nature and lower levels of nature connectedness (Zsido et al 2022 ). For a country-level indicator, the risk of natural disasters was included as an exploratory indicator of potential fear of nature.…”
Section: Introductionmentioning
confidence: 99%
“…However, only emotional nature connection promoted tolerance of the charismatic and benign tapirs and macaws, and only traditionalism and universalism promoted tolerance of the uncharismatic vine snakes (benign) and vipers (threatening). Although people have evolved to fear snakes (Barrett & Broesch, 2012), in Hungary, where wild snakes present minimal risks to lay people (Malina et al., 2008), stronger nature connection has been associated with lower fear of snakes and spiders (Zsido et al., 2022). However, for rural Amazonians, the fear of snakes is easily reinforced through experience, due to a high incidence of snakebites, which may be fatal or cause life‐changing injuries (Feitosa et al., 2015).…”
Section: Discussionmentioning
confidence: 99%